The optimum planting date of sorghum in association with perennial cotton - Beltrão, Napoleão Esberard de Macedo; Azevedo, Demóstenes Marcos Pedrosa de; Nóbrega, Laudemiro Baldoíno da (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this investigation was to study the optimum Sorghum (Sorghum bicolor (L) Moench) sowing date and its influence on perennial cotton (Gossypium hirsutum (L.) marie galante Hutch) when cultivated together in an associated system. An experiment was planted in a brown noncalcareous soil for a period of three years in Patos-PB, Brazil, a geographically distinctive zone of the Seridó. For the first year the rainfall (621.7 mm) was concentrated in March. The treatments consisted of four planting dates for the sorghum, at 15-day intervals, in reference to the planting date of the cotton which was February 15. The spacing was 2 x 1 m., with two plants per furrow for the cotton, with the sorghum in a continuous row in the middle of the cotton. The results showed that the sorghum crop was very competitive resulting in reductions on the growth and development of the cotton plants, specially when planted at the same time. When planted 15 days after cotton, the sorghum competition appeared to be reduced and a yield equilibrium between the two cops was reached. It was observed also that, after the second year, the residual inhibitory influence of the sorghum on perennial cotton desappeared.